Boosting The Welfare of Business Community: Implementing The Model of Islamic Micro Bank of Waqf in Pesantren - Fatira, Marlya; Nasution, Anriza Witi (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Purpose: The Paper is to study the Ability of micro waqf bank (BWM) in boosting The Welfare of Community Business Group at the Islamic Boarding School.Design/Method/Approach : This study uses a descriptive analysis. It intensively Implemented a qualitative approach to obtain information and collected the data needed through conducting interviews directly with informants. Both Observation and library study also applied to extent the secondary data. These methods were conducted to look at the Micro waqf bank model in Islamic boarding schools in Java of whether is able in boosting The Welfare of Business Community around the Islamic boarding school.Findings: The Islamic Boarding School-based Micro-Waqf Bank Model in Java that was applied for community empowerment was carried out a productive financing models in order to make communities able to manage the business–with a financing value of 1-3 million rupiah, within a maximum period of 1 year and payment per week with a maximum margin value equal to 3%. Building a Micro Waqf Bank in the Pesantren can perform through collecting a set of data of cooperative business entities in boarding schools, obtaining LKMS business licenses, obtaining funding for the establishment of BMW, selecting financing customers, and conducting training for selected customers of BWM financing.Originality/Values: The main contribution of this study concern on filling the gap of how the micro bank of waqf efectivelly boost the welfare the bussiness community in pesantren.